Fiber Reinforced Polymers The Technology Applied for Concrete Repair - Alberto Masuelli, Martin (IntechOpen, 2013)
Fiber Reinforced Polymers are by no means new to this world. It is only because of our fascination with petrochemical and non-petrochemical products that these wonderful materials exist. In fact, the polymers can be considered and used in the construction and construction repair. The petrochemical polymers are of low cost and are used more that natural materials. The Fiber Reinforced Polymers research is currently increasing and entails a quickly expanding field due to the vast range of both traditional and special applications in accordance to their characteristics and properties. Fiber Reinforced Polymers are related to the improvement of environmental parameters, consist of important areas of research demonstrating high potential and particularly great interest, as civil construction and concrete repair.